Feasibility of Jatropha and Rice bran vegetable oils as sustainable EDM dielectrics. Issue 1 (2nd January 2023) - Chakraborty, Tapas; Sahu, Deepti Ranjan; Mandal, Amitava; Acherjee, Bappa
ABSTRACT: Electrical discharge machining (EDM) is a nontraditional machining process used for machining hard conductive materials by employing an electrically conductive tool and dielectric. In present days, biodielectric fluids are being used as substitutes with some exceptional attributes in EDM. In that context, the objective of the current work is to study the effectiveness of vegetable oil as dielectric fluid in EDM. In this article, experiment has been conducted using Jatropha biodiesel (Jatropha BD), Rice bran biodiesel (Rice bran BD) and EDM oil as dielectric fluid. The experimental results have reported that the material removal rate (MRR) patterns of Jatropha BD and Rice bran BD oil are almost similar to those of EDM oil, whereas in most of the cases, Jatropha BD displays better surface quality than the Rice bran BD oil. However, both the vegetable oils show superior surface quality compared to EDM oil. Evolvements of unhygienic and toxic gases and generation of nonbiodegradable wastes are few of the critical issues for inferior sustainability and biodegradability of dielectrics. Based on the test results of dissolved gas analysis, transesterified Jatropha oil and Rice Bran oil have been introduced as sustainable and biodegradable dielectrics in EDM.